1999
DOI: 10.1142/s096031319900012x
|View full text |Cite
|
Sign up to set email alerts
|

Screen Printing Process Design of Experiments for Fine Line Printing of Thick Film Ceramic Substrates

Abstract: Screen printing has been the dominant method of thick film deposition because of its low cost. Many experiments in industry have

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 4 publications
(3 reference statements)
2
38
0
4
Order By: Relevance
“…The samples were printed using screen printing technique, M&R Sportsman E Series six-color printing machine. PAN, et al [27] found that four main parameters have a crucial effect on screen print quality. These parameters were kept constant during the printing of all samples.…”
Section: Methodsmentioning
confidence: 99%
“…The samples were printed using screen printing technique, M&R Sportsman E Series six-color printing machine. PAN, et al [27] found that four main parameters have a crucial effect on screen print quality. These parameters were kept constant during the printing of all samples.…”
Section: Methodsmentioning
confidence: 99%
“…It was printed using screen printing technique, M&R Sportsman E-Series six-colour printing machine. Pan et al [11] found that four main parameters have a crucial effect on screen print quality. These parameters were kept constant during the printing.…”
Section: Methodsmentioning
confidence: 99%
“…Print speed, squeegee hardness, squeegee pressure and the distance between the screen and printing substrate (snap-off distance) affect print quality. These parameters all affect the quality, but Pan et al [11] pointed out that the greatest impact on the quality has squeegee hardness and printing speed. In addition to these parameters, printing screen mesh counts and fiber thickness affects the final ink density and tone value reproduction [12].…”
Section: Introductionmentioning
confidence: 99%
“…The samples were printed using the screen printing technique, M&R Sportsman E Series six-colour printing machine. Pan et al found that four main parameters had a crucial effect on the screen print quality [26]. These parameters were kept constant during the printing process of all samples.…”
Section: Experimental Partmentioning
confidence: 99%